Characteristics and the overview of air traffic in the Republic of Croatia - Naletina, Dora (Array, 2018)
As one of the largest and most important industries in the world, the air industry’s impact on economic development, living standard and productivity in the Republic of Croatia has been significant. Air transport is of high significance for the economic development of the Republic of Croatia because its tremendous importance in the development of one of the most important economic branches in Croatia – tourism. Due to the liberalization of the air transportation market in the European Union the growth of low-cost carriers has been noteworthy. The aforementioned liberalization has had a significant impact on the Croatian air transportation market, especially on the presence of low-cost carriers in the coastal Croatian airports. Based on the secondary data analysis, the purpose of this paper is to underline the characteristics of the Croatian air transportation market, and as well to analyse the importance and the role of low-cost carriers in the traffic of all Croatian airports. Due to this development, a significant increase has been noted in the passenger air traffic and as well in the number of low-cost carriers that are offering their services on the Croatian market.